Effect of Fuel Exposure on Oil Company Workers - Ogbutor Godsday; Ndubuishi Christabel; Nwose Junior; Anastacia Ojimba; Isaac Precious; Erumi Selly-U; Ogbutor Godson (Journal of Health and Environmental Research, 2026)
Background: Occupational exposure to petroleum products poses substantial physiological risks to oil company workers. Aim: This study assessed the physiological effects of fuel exposure among oil company workers in Delta State, Nigeria. Methods: This study employed a comparative cross-sectional design involving 330 participants comprising 165 exposed workers (fuel attendants, refinery workers, and maintenance/technical staff) and 165 non-exposed academic staff of Delta State University, Abraka, serving as controls. Measurements of systolic and diastolic blood pressure (SBP and DBP), pulse rate (PR), oxygen saturation (SpO 2 ), peak expiratory flow rate (PEFR), and body temperature were obtained, alongside assessment of clinical symptoms across four physiological domains. Data were analyzed using independent t-tests and chi-square tests at p < 0.05. Results: Exposed workers demonstrated significantly higher mean SBP (136.5 ± 14.2 vs. 124.3 ± 11.8 mmHg), DBP (88.7 ± 9.6 vs. 79.5 ± 8.4 mmHg), PR (84.2 ± 10.5 vs. 76.8 ± 8.9 bpm), and body temperature (37.2 ± 0.4 vs. 36.8 ± 0.3°C) compared to controls (all p < 0.001). Conversely, SpO 2 (94.8 ± 2.1 vs. 97.1 ± 1.5%) and PEFR (410.6 ± 65.3 vs. 465.2 ± 58.7 L/min) were significantly lower in exposed workers (p < 0.001). Chi-square analysis revealed significantly higher prevalence of respiratory (χ 2 = 42.67), neurological (χ 2 = 46.18), and dermatological symptoms (χ 2 = 32.54), and overall physiological symptom burden (χ 2 = 52.89) among exposed workers (all p < 0.001). These findings demonstrate that occupational fuel exposure significantly impairs multi-system physiological function.